Espaço, violência e identidade em Alexandria: um estudo sobre o Conflito de 38 d.C. - Sena, Nicodemo Valim de (2016)
In this dissertation, we analyze the relationship between space, violence and cultural identity during the conflict occurred in A.D. 38 in Alexandria, capital of the province of Egypt, which involved Greeks, Egyptians and Jews. Thus, the bibliographic resource were the works In Flaccum and Legatio ad Gaium, Philo of Alexandria; the work Contra Apionem of Flavius Josephus; the Acta Alexandrinorum and Claudio's Letter to the Alexandrians. Alexandria was built in 331 BC, and during the Ptolemaic rule, achieved great prominence in the political, economic and cultural fields, which attracted a large number of individuals of various ethnic groups, making it a multiethnic city. In this context, investigate the process of formation of communities Greek, Egyptian and Jewish, the singularities of each group, the approaches and how social relations became after Roman rule in 30 BC The theoretical framework used in this research is guided the concepts of "established", "outsiders", "conflict", "violence", "space", "identity" and "difference". Since the methodology used is the Content Analysis. The main objective is to understand how the appropriation of different spaces of the city and the use of violence contributed to the formation and identity affirmation of the social actors involved in the revolt.